2012
DOI: 10.1021/tx300259x
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic Bypass of 8-Oxo-7,8-dihydroguanine (8-Hydroxyguanine) by DNA Polymerase κ in Human Cells

Abstract: The formation of 8-oxo-7,8-dihydroguanine (GO, 8-hydroxyguanine) in DNA and in the nucleotide pool results in G:C→T:A and A:T→C:G substitution mutations, respectively, since GO can pair with both C and A. In this study, the role of DNA polymerase κ in the mutagenicity of GO was investigated, using a supF shuttle plasmid propagated in human U2OS cells. This translesion synthesis DNA polymerase was knocked down by siRNA, and plasmid DNAs containing GO:C and GO:A pairs were transfected into the knock-down cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 50 publications
4
21
0
Order By: Relevance
“…Oxidative damage in DNA is the first culprit to induce such endogenous DNA lesions. However, 8‐oxoguanine, a typical oxidative DNA damage, is shown to be bypassed by Polk in an error‐prone manner [Jaloszynski et al, ; Vasquez‐Del Carpio et al, ; Kamiya and Kurokawa, ]. Therefore, we speculate that oxidative DNA damage in the guanine base other than 8‐oxoguanine is responsible for the elevation in frequencies of G:C to T:A and G:C to C:G mutations in the liver of aged inactivated Polk KI mice.…”
Section: Discussionmentioning
confidence: 80%
“…Oxidative damage in DNA is the first culprit to induce such endogenous DNA lesions. However, 8‐oxoguanine, a typical oxidative DNA damage, is shown to be bypassed by Polk in an error‐prone manner [Jaloszynski et al, ; Vasquez‐Del Carpio et al, ; Kamiya and Kurokawa, ]. Therefore, we speculate that oxidative DNA damage in the guanine base other than 8‐oxoguanine is responsible for the elevation in frequencies of G:C to T:A and G:C to C:G mutations in the liver of aged inactivated Polk KI mice.…”
Section: Discussionmentioning
confidence: 80%
“…These results indicated that DNA pols η and ζ are involved in error-free bypass of the G O base during the replication of ds DNA (Table 1). In contrast, the G ➔T mutation induced by the oxidized base in the ds shuttle plasmid decreased in the DNA pol κ-knockdown human U2OS cells [28]. This result suggested that DNA pol κ bypasses the G O base in an error-prone manner.…”
Section: Introductionmentioning
confidence: 99%
“…pol accurately and efficiently incorporates nucleotides opposite UV-induced cyclobutane pyrimidine dimers (24,25). In addition, pols and are involved in error-prone and errorfree TLS, respectively, of 8-oxo-dG in vivo; pol knockdown reduces G to T transversion mutations caused by 8-oxo-dG in human cells (26), and the absence of pol decreases the accuracy of TLS across 8-oxo-dG in yeast (27).…”
mentioning
confidence: 99%